2021
DOI: 10.1371/journal.pone.0250370
|View full text |Cite
|
Sign up to set email alerts
|

Predicting breast cancer 5-year survival using machine learning: A systematic review

Abstract: Background Accurately predicting the survival rate of breast cancer patients is a major issue for cancer researchers. Machine learning (ML) has attracted much attention with the hope that it could provide accurate results, but its modeling methods and prediction performance remain controversial. The aim of this systematic review is to identify and critically appraise current studies regarding the application of ML in predicting the 5-year survival rate of breast cancer. Methods In accordance with the PRISMA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 76 publications
(163 reference statements)
2
49
0
7
Order By: Relevance
“…15 There are several AI strengths highlighted in the literature; however, limitations of the existing prediction models have also been noted due to the lack of data and concerns with validation and promotion (Table 1). 16,17 Several studies in the literature showed that AI-based applications will not replace radiologist's role; in fact, it will improve radiology services and radiologists' performance. 18 However, other researchers were worried that AI-based applications could be influencing medical students' decisions from choosing radiology as aprofession.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 There are several AI strengths highlighted in the literature; however, limitations of the existing prediction models have also been noted due to the lack of data and concerns with validation and promotion (Table 1). 16,17 Several studies in the literature showed that AI-based applications will not replace radiologist's role; in fact, it will improve radiology services and radiologists' performance. 18 However, other researchers were worried that AI-based applications could be influencing medical students' decisions from choosing radiology as aprofession.…”
Section: Introductionmentioning
confidence: 99%
“… 15 There are several AI strengths highlighted in the literature; however, limitations of the existing prediction models have also been noted due to the lack of data and concerns with validation and promotion ( Table 1 ). 16 , 17 …”
Section: Introductionmentioning
confidence: 99%
“…In a performance comparison performed by Asri et al [ 123 ], different ML methods for breast cancer risk profiling and diagnosis were compared, showing support vector machine (SVM) to have the highest accuracy (97.13%) and the least associated error. In a systemic review by Li et al [ 124 ] regarding the application of ML for the prediction of five-year survival rates in breast cancer, decision trees were shown to be most frequently deployed (61.3%), followed by deep learning (58.1%), support vector machines (51.6%), and ensemble learning (32.3%). An accuracy of 0.510–0.971, sensitivity of 0.037–1 and a specificity of 0.008–0.993 was seen with an AUC ranging from 0.500–0.972.…”
Section: Whole Slide Imaging Radiomics and Multi-omic Machine Learningmentioning
confidence: 99%
“…We found that most of the reported 5-year survival prediction models for breast cancer have considered data preprocessing, feature selection, class imbalance processing, and model validation. [24]. We only find two studies that were further verified externally[25, 26].…”
Section: Introductionmentioning
confidence: 95%